The translation peculiarities of the poem Olzhas Suleymenov «Adamga tabyn, Zher endi» (Eurasian Journal of Philology Science and Education, 2016)
The translation specifics of the poem about first cosmonaut Yuriy Gagarin done by Olzhas Omarkhanuly Suleymenov is thoroughly written in this article. Olzhas is a Russian languaged poet. It is known than the poet’s works have been translated into many languages. He reads his compositions in Russian language. What kind of methods were used by a talented poet Kadyr Nyrza Ali, who translated the poem into Kazakh, achiements and disadvantages of translation was analyzed by concrete example.
Keywords: translation; poem; poet; interpreter; free translation